The Impact of the Pandemic on Service Quality and Dental Patient Satisfaction - Helmi Aryo; Hutomo, MM Suryani; Nugroho, Daniel Chriswinanto Adityo (Poltekkes Kemenkes Tanjung Karang, 2025)
The quality of health services plays a crucial role in determining patient satisfaction. During the Covid-19 pandemic, dental services faced additional challenges due to limited access and the risk of infection, which could affect patient satisfaction. This study aims to analyze the relationship between dental service quality and patient satisfaction during the Covid-19 pandemic. A correlational analytic design was applied with a purposive sample of 40 patients who visited the dental polyclinic. Data were collected using a service quality questionnaire that covered five dimensions (tangibles, reliability, responsiveness, assurance, and empathy) and the Patient Satisfaction Questionnaire (PSQ-18), which assessed seven aspects of satisfaction. Data analysis used the Pearson correlation test. Results showed that service quality was perceived as low in the tangible dimension (27%), but high in responsiveness (47.5%), assurance (49%), and empathy (48%). Patient satisfaction was mostly reported as being generally satisfied in terms of technical quality (47.5%), interpersonal manner (47.5%), financial aspects (46.2%), communication (40%), and time with the doctor (52.5%), while accessibility was rated as neutral (38.75%). Statistical analysis revealed a strong positive relationship between service quality and patient satisfaction (r=0.772; p<0.05). Dental service quality has a significant impact on patient satisfaction, with the tangible dimension requiring further improvement. It is recommended that healthcare providers enhance facility cleanliness, equipment maintenance, and overall comfort to better meet patient expectations. Future research should include larger samples and different settings to allow broader generalization.